(untitled) (Research, Society and Development, 2021)
Eating behavior is influenced by several factors, such as psychological, emotional, or socioeconomic, it means that lifestyle guides eating. The initiation into academic life makes these feelings wider, due to stress to fitthe body in the imposed standards, it added to the expectations of a good professional performance, especially about students of Nutrition area. The objective of this research was to analyze behavioral changes of Nutrition students during the course, linked to eating habits and lifestyle. 37 nutrition students from a private institution in Pindamonhangaba - SP, who were enrolled in different periods, were evaluated. The questionnaires Eating Attitudes Test (EAT-26) and Body Shape Questionnaire (BSQ) were applied to analyze eating disorders and body image disturbance, respectively, as well as a Food Frequency Questionnaire and another one with personal questions about social profile and lifestyle. Descriptive and statistical analysis of the results was carried out to verify the association between the behavioral change of eating habits and lifestyle of nutrition students during the course. Although results of mild eating disorders and body image dissatisfaction were found in all periods, there was no significant difference between the classes assessed and no significant presence of these disorders in the group. However, the eating habits, and consequently, the nutritional status of most of these students, are adequate, a fact that may have been influenced by the acquisition of new knowledge in the area.